Female athlete representation and dietary control methods among studies assessing chronic carbohydrate approaches to support training - Kuikman, M. A.; McKay, A. K.; Smith, E. S.; Ackerman, K. E.; Harris, R.; Elliott-Sale, K. J.; Stellingwerff, T.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2023)
The aim of this audit was to assess the representation of female athletes, dietary control methods, and gold standard female methodology that underpins the current guidelines for chronic carbohydrate (CHO) intake strategies for athlete daily training diets. Using a standardized audit, 281 studies were identified that examined high versus moderate CHO, periodized CHO availability, and/or low CHO, high fat diets. There were 3,735 total participants across these studies with only ~16% of participants being women. Few studies utilized a design that specifically considered females, with only 16 studies (~6%) including a female-only cohort and six studies (~2%) with a sex-based comparison in their statistical procedure, in comparison to the 217 studies (~77%) including a male-only cohort. Most studies (~72%) did not provide sufficient information to define the menstrual status of participants, and of the 18 studies that did, optimal methodology for control of ovarian hormones was only noted in one study. While ~40% of male-only studies provided all food and beverages to participants, only ~20% of studies with a female-specific design used this approach for dietary control. Most studies did not implement strategies to ensure compliance to dietary interventions and/or control energy intake during dietary interventions. The literature that has contributed to the current guidelines for daily CHO intake is lacking in research that is specific to, or adequately addresses, the female athlete. Redressing this imbalance is of high priority to ensure that the female athlete receives evidence-based recommendations that consider her specific needs.